Isolamento de myxovirus parainfluenza 3 de gado bovino no Estado de São Paulo, Brasil Isolation of Myxovirus parainfluenza type 3 from cattle in S. Paulo State, Brazil - José Alberto N. Candeias; Washington Sugay; Luiz Conrado Ribeiro (Universidade de São Paulo, 1971)
Faz-se referência ao isolamento, em São Paulo, de 4 cêpas de Myxovirus parainfluenza do tipo 3, do tecido pulmonar de gado bovino com lesões de pneumonia, que se mostraram antigenicamente semelhantes à cêpa bovina SF-4. Uma das cêpas isoladas mostrou certa relação antigênica com a cêpa humana HA-1. The isolation of Myxovirus parainfluenza type 3 from cattle with pneumonia, in S. Paulo, Brazil, is reported. All the strains isolated appeared to be antigenically related to the bovine strain SF-4. It was possible to establish a certain degree of antigenic relationship between the human strain HA-1 and one of the bovine strains isolated.